Identifying the Novel Inhibitors Against the Mycolic Acid Biosynthesis Pathway Target “mtFabH” of Mycobacterium tuberculosis - Kumar, Niranjan; Srivastava, Rakesh; Mongre, Raj Kumar; Mishra, Chandra Bhushan; Kumar, Amit; Khatoon, Rosy; Banerjee, Atanu; Ashraf-Uz-Zaman, Md; Singh, Harpreet; Lynn, Andrew M.; Lee, Myeong-Sok; Prakash, Amresh (Frontiers in Microbiology, 2022)
Mycolic acids are the key constituents of mycobacterial cell wall, which protect the bacteria from antibiotic susceptibility, helping to subvert and escape from the host immune system. Thus, the enzymes involved in regulating and biosynthesis of mycolic acids can be explored as potential drug targets to kill Mycobacterium tuberculosis (Mtb). Herein, Kyoto Encyclopedia of Genes and Genomes (KEGG) is used to understand the fatty acid metabolism signalling pathway and integrative computaional approach to identify the novel lead molecules against the mtFabH (beta-ketoacyl-acyl carrier protein (ACP) synthase III, the key regulatory enzyme of the mycolic acid pathway. The structure-based virtual screening of antimycobacterial compounds from ChEMBL library against mtFabH results in the selection of 10 lead molecules. Molecular binding and drug-likeness properties of lead molecules compared with mtFabH inhibitor suggest that only two compounds, ChEMBL414848 (C1) and ChEMBL363794 (C2) may be explored as potential lead molecules. However, the spatial stability and binding free energy estimation of Thiolactomycin (TLM), compounds C1 and C2 with mtFabH using molecular dynamics simulation, followed by Molecular mechanics Poisson–Boltzmann surface area indicate the better activity of C2 (∆G = -14.18 kcal/mol) as compared to TLM (∆G = -9.21 kcal/mol) and C1 (∆G = -13.50 kcal/mol). Thus, compound C1 may be explored as promising drug candidate for the structure-based drug designing of mtFabH inhibitors in the therapy of Mtb.